Pengembangan bahan ajar science, technology, engineering, mathematics model project-based learning untuk meningkatkan proses sains ditinjau dari kemampuan awal dan sikap ilmiah - Rusli Irwanto; Ishafit Ishafit; Moh. Toifur (Berkala Fisika Indonesia : Jurnal Ilmiah Fisika, Pembelajaran dan Aplikasinya, 2023)
This research aims to develop teaching materials for project-based learning models for science, technology, engineering, and mathematics (STEM). The procedure for developing teaching materials refers to the 4D model (Design, Define, Develop, Disseminate). The research instrument was in the form of teaching material validation sheets and science process skills tests. The design used is a non-equivalent (pretest-posttest) design. Data were analyzed using due diligence and effectiveness analysis. The product, as a result of the development, was tested and involved two covariates: initial ability and scientific attitude. The developed teaching materials have a very valid category, and the feasibility value of the science process skills test questions from the validator is 97% very good category. The resulting product is practical to apply based on the results of learning management. PjBL STEM teaching materials can improve science process skills.